2022
DOI: 10.1109/access.2022.3222782
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancement of Wearable Reconfigurable Antenna Technologies: A Review

Abstract: Wireless Body Area Network (WBAN) technology is gaining popularity in personal communication due to the expanding improvement in wireless technology. Wearable antennas are utilized in various WBAN applications including personal healthcare, entertainment, military, and many more due to their attractive characteristics and the potential for integrating lightweight, compact, low-cost, and adaptable wireless communications. A wearable reconfigurable antenna will allow a single antenna to operate at multiple reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 132 publications
0
24
0
Order By: Relevance
“…21 shows the simplified human body tissue model made up of four layers: skin, fat, muscles, and bones. Their details and thickness were obtained from [7]. Table 5 shows the simulated SAR limits for 1 g and 10 g of human tissue at the resonant frequencies under varying input power.…”
Section: Sar Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…21 shows the simplified human body tissue model made up of four layers: skin, fat, muscles, and bones. Their details and thickness were obtained from [7]. Table 5 shows the simulated SAR limits for 1 g and 10 g of human tissue at the resonant frequencies under varying input power.…”
Section: Sar Analysismentioning
confidence: 99%
“…From the figure, there is a slight shift on the S11 when it is placed directly on the arm. This is due to human tissue having a high dielectric constant, which explains the changes in the lower resonant frequency [7]. Moreover, the radiation patterns when the antenna is placed on human body tissue model were also simulated (the antenna is placed directly on the skin and also on different garment's thickness from 2 mm to 10 mm), as shown in Fig.…”
Section: Antenna's Performance Near Human Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…A nonlinear device's linear operating range is defined as the input-output power range that allows the device to function while preserving a linear relationship between its input and output power. The input power level at which the device's output power is lowered by 1-dB from the output power of the ideal device is known as the P 1-dB [37]. The measurement revealed that the P 1-dB could not be found at 2.4 GHz, which implies that the antenna behaves linearly within the range of input power, as shown in Figure 18a.…”
Section: Measurement Of P 1-dbmentioning
confidence: 99%
“…As a result, exible dielectric materials were used to create wearable exible antennas, which were also built employing exible conductive materials for the patch and ground plane. The main requirements for wearable materials are their small size, exibility, robustness, and low power needs while maintaining the wearer's comfort Musa et.al [15]. For the development of exible antennas, textile wearable materials are preferred over other materials.…”
Section: Introductionmentioning
confidence: 99%